Numerical simulation and performance optimization of a solid-state dye-sensitized solar cell with iridium counter electrode - Bethuel S.K. Langa; Azile Nqombolo; Edson L. Meyer; Mojeed A. Agoro; Nicholas Rono (Results in Surfaces and Interfaces)
To address high global demand for energy, enormous efforts have been dedicated to the development and adoption of renewable energy sources including solar cell technologies. This study theoretically investigates Iridium (Ir) metal with work function of 5.27 eV as counter electrode in ss-DSSCs using the SCAPS-1D software. The electron transport layers (ETLs) proposed and tested included SnO2, CdS, CdZnS, and ZnSe, while the ruthenium-based dye N719 served as the absorber. Additionally, various hole transport layers (HTLs) were evaluated, specifically Cu2O, spiro-OMeTAD, CZTS, and CZTSe in a novel n-i-p solar device with general structure of FTO/ETL/N719/HTL/Ir. The best performing ETL material was SnO2 while, the best HTL material was identified as CZTS. Ultimately, the optimized device FTO/SnO2/N719/CZTS/Ir achieved an open circuit voltage (Voc) of 5.409 V, a short circuit current density (Jsc) of 28.87 mA cm⁻2, a power conversion efficiency (PCE) of 22.91%, and a fill factor (FF) of 14.64%. In contrast the devices using Cu2O, spiro-OMeTAD and CZTSe achieved in PCEs of 15.61, 14.97, and 22.51% respectively. The optimal density of defects of absorber (Nt) was maintained at 5 × 1016 cm−2, while, the CZTS-based device reached efficiency above 20% across a temperature range of 280–400 K. The exploration of various metal work function for Au, Ni, Pd, and Pt exhibited PCE of 21.04, 22.41, 23.07, and 21.56% respectively, demonstrating comparable performance to the Ir back contact. These theoretical findings can provide insights into sustainable pathways for the fabrication of ss-DSSCs using recycled iridium as a counter electrode.